Pharmacokinetics, safety, and efficacy of Fuqi Guben Gao in the treatment of kidney-yang deficiency syndrome: a randomized, double-blind phase I trial - Cao, Wei-Yi; Liu, Jun-Yu; Sun, Min; Wang, Jing-Kun; Lu, Fang; Yang, Qiao-Ning; Zhang, Wan-Tong; Zi, Ming-Jie; Zhang, Bai-E; Liu, Hong-Bin; Wang, Shu-Ge; Wu, Yi; et al. (Frontiers in Pharmacology, 2024)
Fuqi Guben Gao (FQGBG) is a botanical drug formulation composed of FuZi (FZ; Aconitum carmichaelii Debeaux [Ranunculaceae; Aconiti radix cocta]), Wolfberry (Lycium barbarum L. [Solanaceae; Lycii fructus]), and Cinnamon (Neolitsea cassia (L.) Kosterm. [Lauraceae; Cinnamomi cortex]). It has been used to clinically treat nocturia caused by kidney-yang deficiency syndrome (KYDS) for over 30 years and warms kidney yang. However, the pharmacological mechanism and the safety of FQGBG in humans require further exploration and evaluation. We investigated the efficacy of FQGBG in reducing urination and improving immune organ damage in two kinds of KYDS model rats (hydrocortisone-induced model and natural aging model), and evaluated the safety of different oral FQGBG doses through pharmacokinetic (PK) parameters, metabonomics, and occurrence of adverse reactions in healthy Chinese participants in a randomized, double-blind, placebo-controlled, single ascending dose clinical trial. Forty-two participants were allocated to six cohorts with FQGBG doses of 12.5, 25, 50, 75, 100, and 125 g. The PKs of FQGBG in plasma were determined using a fully validated LC-MS/MS method. FQGBG significantly and rapidly improved the symptoms of increased urination in both two KYDS model rats and significantly resisted the adrenal atrophy in hydrocortisone-induced KYDS model rats. No apparent increase in adverse events was observed with dose escalation. Major adverse drug reactions included toothache, thirst, heat sensation, gum pain, diarrhea, abdominal distension, T-wave changes, and elevated creatinine levels. The PK results showed a higher exposure level of benzoylhypaconine (BHA) than benzoylmesaconine (BMA) and a shorter half-life of BMA than BHA. Toxic diester alkaloids, aconitine, mesaconitine, and hypaconitine were below the lower quantitative limit. Drug-induced metabolite markers primarily included lysophosphatidylcholines, fatty acids, phenylalanine, and arginine metabolites; no safety-related metabolite changes were observed. Under the investigated dosing regimen, FQGBG was safe. The efficacy mechanism of FQGBG in treating nocturia caused by KYDS may be related to the improvement of the hypothalamus-pituitary-adrenal axis function and increased energy metabolism.